Analysis of Asset Growth Anomaly on Cross-Section Stock Returns: Evidence from Indonesia Stock Exchange - Muhammad Iqbal; Buddi Wibowo (Universitas Hayam Wuruk Perbanas, 2016)
Assorted types of market anomalies occur when stock prices deviate from the prediction of classical asset pricing theories. This study aims to examine asset growth anomaly where stocks with high asset growth will be followed by low returns in the subsequent periods. This study, using Indonesia Stock Exchanges data, finds that an equally-weighted low-growth portfolio outperforms high-growth portfolio by average 0.75% per month (9% per annum), confirming existence of asset growth anomaly. The analysis is extended at individual stock-level using fixed-effect panel regression in which asset growth effect remains significant even with controlling other variables of stock return determinants. This study also explores further whether asset growth can be included as risk factor. Employing two-stage cross-section regression in Fama and Macbeth (1973), the result aligns with some prior studies that asset growth is not a new risk factor; instead the anomaly is driven by mispricing due to investorsâ€™ overreaction and psychological bias. This result imply that asset growth anomaly is general phenomenon that can be found at mostly all stock market but in Indonesia market asset growth anomaly rise from investorsâ€™ overreaction, instead ofÂ playing as a factor of risk.